HR Strategies to Support Creativity and Innovation: Evaluation Based on Ambidextrous Organisational Theory and Knowledge Management - Paroli, Paroli (International Journal of Economics (IJEC), 2025)
Innovation and creativity are important keys to the sustainability and competitiveness of organisations, especially in the face of rapid change and global competition. This study aims to evaluate the role of Human Resource (HR) strategy in supporting organisational creativity and innovation, by relating it to the theory of ambidextrous organisation and knowledge management. The type of research used is qualitative descriptive research with a literature review approach. The research population includes articles and previous studies relevant to the research topic, obtained from leading academic databases such as Google Scholar, Scopus, and JSTOR. The sampling technique used is purposive sampling, with a total of 30 literature samples selected based on the relevance and quality of the sources. The results show that HR policies that support exploration and exploitation can create a culture of sustainable innovation. In addition, effective knowledge management, both explicit and tacit, plays an important role in accelerating the innovation process and increasing the organisation's capacity to adapt. This research provides practical implications for organisations to formulate more flexible HR strategies and encourage effective collaboration through knowledge sharing between employees.